Odnalezione wzory graficzne późnorenesansowych polichromii w tzw. Piwnicy pod Fortuną w kamienicy Lubomelskich w Lublinie (Tabularium Historiae, 2018)
The cellar “Under the Fortuna” is located at 8 Rynek Street, right in the center of the Old Town district of Lublin. Its interior partly preserves secular late -Renaissance wall paintings. Even though it has been known for decades it has never received a thorough examination by scholars. The most extensive study concerning the paintings so far was published in 1957 by Józef Edward Dutkiewicz (Malowidła z XVI w. w tzw. winiarni w Lublinie / The 16th C. Murals in the So-Called Winery in Lublin).